Real Flight Application of a Monocular Image-Based Aircraft Collision Decision Method - Peter Bauer; Antal Hiba; Tamas Zsedrovits (International Journal of Aerospace Engineering)
This paper considers real flight application of a monocular image-based aircraft collision decision algorithm developed in a previous paper. First, it briefly summarizes the theory based on the previous paper and extends the results with a detailed evaluation of possible special cases. Second, it introduces the UAVs and flight test scenarios together with the camera system and the steps of image processing used in flight testing. A brief analysis about intruder detectability is also provided referencing a more exhaustive work of the authors. The main contribution is the detailed comparison of the image-based estimated collision parameters to the flight trajectory-based ones together with threshold selection for collision decision. Different threshold combinations are evaluated offline, and finally, real flight decision results based on one of the threshold combinations are also discussed. The paper ends with the setup of future research directions.